Kompetensi Digital sebagai Prediktor Niat Digipreneurship: Studi pada Mahasiswa Manajemen di Era Ekonomi Digital - Ahmad Nasori (Jurnal Manajemen dan Ekonomi Kreatif, 2026)
This study aimed to examine the relationship between digital competence and digipreneurship intention among management students in higher education. A quantitative correlational survey design was employed to investigate the association between the two variables. Data were collected from 59 management students using two validated instruments. Digital competence was measured using the Indonesian version of the Student Digital Competence Scale (SDiCoS), which consists of 28 items across six dimensions based on the DigComp framework. Digipreneurship intention was assessed using a 15-item scale developed from the Entrepreneurial Event Model (EEM) and Self-Determination Theory (SDT), covering five dimensions of entrepreneurial intention in digital contexts. Descriptive analysis revealed that students demonstrated a high level of digital competence (M = 4.07, SD = 0.57) and a similarly high level of digipreneurship intention (M = 3.97, SD = 0.49). Spearman correlation analysis indicated a statistically significant positive relationship of moderate strength between digital competence and digipreneurship intention (rs = .445, p < .01). Reliability testing showed excellent internal consistency for both instruments, with Cronbach’s alpha coefficients of .959 for the SDiCoS and .908 for the digipreneurship intention scale. These findings suggest that enhancing students’ digital competence, particularly in data management and digital security, may contribute to strengthening their intention to engage in digital entrepreneurship. The study highlights implications for curriculum development and digital entrepreneurship education in higher education institutions. Nevertheless, limitations related to sample size and respondent scope indicate the need for future studies involving larger and more diverse populations.